Clinical Characteristics of COVID-19 Patients in Dr. Saiful Anwar Hospital, Malang - Magdalena Magdalena; Yani Jane Sugiri; Rezki Tantular; Aditya Listyoko (Jurnal Respirologi Indonesia, 2021)
Background: Coronavirus Disease (COVID-19) emerge as a new global health crisis. COVID-19 has a wide range of clinical feature, from mild cough to severe respiratory failure. This study aims to learn more about clinical feature of COVID-19. Methods: This cross sectional analytic descriptive study includes all COVID-19 patients that yield positive result through GeneXpert-SARS-CoV-2 or Polymerase Chain Reaction (PCR). All data was taken from inpatient form March 12th –June 30th 2020. Results: There were 103 patients with 58 men and 45 women. Patients with male sex tend to experience severe pneumonia than women. It was also found that patients exposed to cigarette smoke tended to experience severe pneumonia symptoms. Patients with more than 1 comorbid tend to develop severe pneumonia symptoms. The dominant clinical symptoms in the patient were cough (84.5%), fever / history of fever (70.9%), and shortness of breath (67.9%). Hematological parameters that correlate with the degree of severity are leucocytes, thrombocyts, lymphocytes, neutrophils, CRP, LDH, creatinine, procalcitonin, SGOT, and SOFA Score. The most common radiological picture obtained was bilateral infiltrate (78.2%). The most common complication was sepsis (38.9%). The mortality rate for COVID-19 patients treated at RSSA tends to be high (26.2%). Discussion: clinical characteristics such as gender, smoking history, comorbides, clinical symptoms (fever, shortness of breath and cough), laboratory (leukocytes, % lymphocytes, % neutrophils and neutrophil counts, CRP, LDH, procalcitonin, creatinine, SGOT, and SOFA scores) has a significant effect on the severity of Covid infection 19 Conclusion: The clinical characteristics of COVID-19 patients affects the severity of the disease.